Pengaruh Kualitas Pelayanan dan Bagi Hasil Terhadap Minat Menabung Masyarakat pada Tabungan Marhamah PT. Bank Sumut Cabang Pembantu Syariah Panyabungan - Putri, Sania Adela; Jannah, Nurul (Regress: Journal of Economics & Management, 2022)
This study aims to determine the effect of service quality and profit sharing on the interest in saving the Panyabungan community on the Marhamah savings of PT Bank Sumut Panyabungan Syariah Branch Office. The dependent variable in this study is the saving interest of the Panyabungan community in Marhamah's savings, while the independent variables consist of service quality and profit sharing. The sample used in this study were 93 customers. This study uses a questionnaire as primary data then the data results are analyzed using linear regression analysismultiple. The results of this study indicate that service quality and profit sharing have a significant effect on the interest of the Panyabungan community to save on Marhamah's savings at PT Bank Sumut Panyabungan Sharia Sub-Branch Office